Research on Diffusion Patterns of Gas Produced by Energy Storage Lithium Batteries due to Thermal Runaway - LIU Li; SHI Mengzhao; XU Dongyang; TANG Wenbing; HU Yue; JIANG Fengbing (Kongzhi Yu Xinxi Jishu)
In order to investigate the reaction characteristics of 25 Ah and 50 Ah lithium iron phosphate (LiFePO4) cells at 100% state of charge (SOC) under the thermal runaway state and to examine the spreading patterns of smoke during the thermal runaway combustion of battery modules within energy storage containers, this paper proposes a research approach combining experimental and simulation methods. In the experimental stage, cells of both capacities are induced into thermal runaway by heating, which is followed by stability observations focusing on the internal reactions of these cells. The subsequent modeling of cell combustion, combined with experimental data, allows for the accurate correction of the heat release rate curve using a modified dichotomy method. In the numerical simulation stage, the corrected heat release rate curve, along with the large eddy simulation (LES) method, is used to simulate the thermal runaway combustion process of battery modules within containers. To sum up, the proposed approach supports the accurate correction of heat release rate curves and can effectively simulate the thermal runaway combustion process of battery modules within containers. A comparison with experimental data reveals that the 50 Ah cells exhibit more uniform and stable reactions compared to the 25 Ah cells, suggesting that larger-capacity cells demonstrate more stable performance during thermal runaway. The data also indicate that, without accounting for ventilation and flame spreading within the containers, the most severe fire occurs inside the prefabricated compartment of the 3000 Ah battery module at the peak of the heat release rate, suggesting that flames could spread throughout the battery rack within 150 seconds. In addition, the smoke layer spreads from the battery compartment to the ground within only 50 seconds.